Intergranular corrosion in AA2024-T3 aluminium alloy: The influence of stored energy and prediction. (15th July 2019) - Zhang, Xinxin; Jiao, Yanbin; Yu, Yang; Liu, Bing; Hashimoto, Teruo; Liu, Hongfang; Dong, Zehua
Highlights: Compared to that with lower stored energy, grain with higher stored energy is more susceptible to corrosion. Copper tends to segregate at dislocations. Grain with higher stored energy displays a more negative surface potential compared to that with lower stored energy. Using stored energy distribution, intergranular corrosion could be predicted. Abstract: In the present work, microstructure and intergranular corrosion behaviour of AA2024-T3 alloy are studied. Using electron diffraction techniques to correlate stored energy distribution with corrosion propagation path, intergranular corrosion tends to occur in the periphery of grain with relatively high stored energy. Further, it is revealed that Cu tends to segregate at dislocations, resulting in high Cu content of grain with high stored energy, which promotes corrosion propagation into its interior. In addition, based on the relationship between stored energy and boundary attack, intergranular corrosion during the immersion in NaCl solution could be successfully predicted.